THE VERB-FORMING AFFIXATION IN SIDETAPA DIALECT OF BALINESE: A MORPHOPHONEMIC ANALYSIS - ., Ni Kadek Ariasih; ., Prof. Dr.I Nyoman Adi Jaya Putra, MA; ., Ni Wayan Surya Mahayanti, S.Pd, M.Pd (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
The study aimed at discovering data and information about the number of prefixes and suffixes found in Sidetapa Dialect of Balinese (SDB) having role in constructing verb. This study was designed by using descriptive qualitative approach. The main informant of this study was one family which was chosen based on certain criteria. The data was collected by means of word lists: Swadesh, Nothofer, Holle, and Budasi and sentence list. Some natural speeches produced among family member with their neighbors and friends were also recorded. The obtained data were analyzed descriptively. The result revealed that there were two prefixes having role in constructing verb, namely: prefix {ma- and N-} and three suffixes {-ng, -a, and -na}. All of the prefixes experienced morphophonemic process in certain condition. Prefix {ma-} underwent morphophonemic process in the form of deleting phoneme /a/ in prefix {ma-} itself when it was added into any base which had an initial vowel. And prefix N- was indicated by its change into some allomorphs namely: |n-|, |ny-|, |ng-|, |m| when they were attached into a particular base. Meanwhile the suffix experiencing morphophonemic process was suffix {-ang}. Each prefix and suffix had more than one meaning depending on the bases attached into it. The usage of each prefix and suffix was also different. It is expected that this study can be used as a reference for the other researchers that interest in exploring more about SDB, especially the availability of the affixes and their changes. Kata Kunci : prefix, suffix, verb formation, morphophonemic process, Sidetapa Dialect of Balinese Penelitian ini bertujuan untuk menemukan data dan informasi tentang jumlah awalan dan akhiran yang mempunyai peran untuk membentuk kata kerja dalam dialek Sidetapa. Penelitian ini dirancang dengan menggunakan pendekatan deskripsi kualitatif. Informan utama dalam penelitian ini yaitu satu keluarga yang dipilih berdasarkan kriteria tertentu. Data dikumpulkan dengan menggunakan daftar kata yang disusun oleh: Swadesh, Nothofer, Holle, and Budasi, daftar kalimat. Beberapa percakapan antara anggota keluarga, anggota keluarga dengan temannya dan juga dengan tetangganya juga direkam. Data yang sudah diperoleh dianalis secara deskriptif. Hail penelitian menunjukkan bahwa terdapat dua awalan yang memiliki peran untuk membuat kata kerja yaitu awalan {ma- and N-} dan tiga akhiran {-ng, -a, and -na}. Semua awalan tersebut mengalami proses morpofonemik dalam beberapa kondisi tertentu. Awalan {ma-} mengalami proses morpofonemik yang ditandai dengan penghilangan fonem [a] terhadap awalan {ma-} itu sendiri ketika awalan tersebut digabungkan dengan kata dasar yang berinisial vowel. Sedangkan awalanN-dicirikan dengan allomorph yang dimilikinya yaitu |n-|, |ny-|, |ng-|, |m| ketika digabungkan dengan kata dasar tertentu. Sedangkan akhiran yang mengalami proses morpofonemik yaitu akhirin {-ang}. Masing-masing awalan maupun akhiran memiliki makna yang bervariasi tergantung dari kata dasar yang dilekatkan. Penggunaanya dari masing-masing awalan maupun akhiran tersebut jga berbeda-beda. Penulis sangat berharap agar penelitian ini bisa dijadikan sebagai acuan bagi peneliti-peneliti lain yang tertarik untuk mengksplor lebih dalam lagi tentang dialek Sidetapa khusunya keberadaan imbuhan-imbuhan dan perubahannya. keyword : awalan, akhiran, pembentukan kata kerja, proses morpofonemik, dialek Sidetapa